Analysis of the effectiveness of existing pond to accommodate storm water runoff in UTHM - Mohd Yusoff, Mohd Azlan; Mohd Bukhari, Saifullizan; Adnan, Mohd Shalahuddin (International Journal of Integrated Engineering, 2018)
Rapid development within UTHM campus has changed the existing earth surface from pervious to impervious layer thus increasing the surface runoff. This study describe the application of XP SWMM software in determining the effectiveness of existing pond to accommodate the increase of storm water runoff based on designated rainfall event. Through this approach, the past studies, related journals, and Storm-water Management Manual (SWMM) are used as a reference for this study. Land and hydrographic survey is carried out in order to determine pond profile. The selected study principle using XPSWMM software is based on Rational Method as the catchment area is less than 80 ha and Manning Equation. The existing pond is designed to receive storm water runoff from two different catchments which are area around University Health Centre (PKU) and area starting from Centre for Diploma Studies (PPD) until Information Technology Centre (PTM). The input rainfall data is for 10 years rainfall event (2006-2016). It was found that there are no overflow from the pond, thus the volume for the pond (12356.39m^3) is effective to accommodate increasing storm water runoff from both catchment area.